Efficiency of using silicon dioxide nanoparticles to increase wheat productivity in soil and climatic conditions of Western Siberia - Tereshchenko, Natalya N.; Makarov, Boris I.; Kravets, Aleksandra V.; Lushchaeva, Inna V.; Minaeva, Oksana M.; Svetlichnyi, Valerii A. (BioNanoScience)
In this study, we investigated the effectiveness of silica nanoparticle (SiO2NP) suspension for pre-sowing inoculation of spring wheat seeds under soil and climatic conditions of the Western Siberia. We report that SiO2NP suspension at concentrations of 3 × 10−7% to 3 × 10−4% does not have a toxic effect on the culture of microalgae Chlorella vulgaris and spring wheat. On the contrary, seed inoculation with nanoparticles increased seed germination by 15-40% relative to the control. The green mass yield of wheat seedlings exposed to SiO2NPs also increased by 5-41% relative to the control. In field experiments, presowing treatment of spring wheat with SiO2NPs at concentrations of 3.0 × 10−4%, 1.5 × 10−4%, and 0.3 × 10−4% increased the main morphometric parameters of plants, such as height and green mass. Seed inoculation with SiO2NPs improved plant productivity: the grain yield in the variant with the minimum (0.3 × 10−4%) and average (1.5 × 10−4%) concentrations of SiO2NPs grew by 20.1% and 18.4%, respectively. Plants inoculated with SiO2NPs showed higher resistance to root rot pathogens (Fusarium oxysporum and Bipolaris sorokiniana): the disease prevalence decreased by 16-33% and the disease incidence index grew by 7-14% relative to the control. Seed inoculation with SiO2NPs increased the content of protein and important biogenic elements such as potassium, calcium, sulfur, phosphorus, and silicon in the grain.